2021
DOI: 10.1038/s41436-021-01272-0
|View full text |Cite
|
Sign up to set email alerts
|

The design, implementation, and effectiveness of intervention strategies aimed at improving genetic referral practices: a systematic review of the literature

Abstract: Purpose Despite rapid advancements in genetics and genomics, referral practices remain suboptimal. This systematic review assesses the extent to which approaches from implementation science have been applied to address suboptimal genetic referral practices. Methods A search of MEDLINE, EMBASE, and PsycINFO generated 7,794 articles, of which 28 were included. Lay barriers were mapped to the Theoretical Domains Framework (TDF) and interventions mapped to beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 76 publications
0
13
0
3
Order By: Relevance
“…Dada raridade de várias doenças genéticas, muitos profissionais de saúde aprenderam pouco sobre o assunto em sua formação e, portanto, têm dificuldade para suspeitar de uma doença genética rara 44 . Mesmo no cenário internacional, o encaminhamento para especialistas em genética está abaixo do ideal, e são apontadas como possíveis barreiras a falta de conhecimento sobre o tema e/ou a inexistência de protocolos de referência 16 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Dada raridade de várias doenças genéticas, muitos profissionais de saúde aprenderam pouco sobre o assunto em sua formação e, portanto, têm dificuldade para suspeitar de uma doença genética rara 44 . Mesmo no cenário internacional, o encaminhamento para especialistas em genética está abaixo do ideal, e são apontadas como possíveis barreiras a falta de conhecimento sobre o tema e/ou a inexistência de protocolos de referência 16 .…”
Section: Discussionunclassified
“…Coletar história familiar completa é uma das habilidades desejáveis a todos os profissionais de saúde 4,12,46 . A inadequada coleta e documentação da história familiar tem sido apontada como um dos obstáculos para o encaminhamento ao especialista em genética 16 . Esse cenário pode levar a perdas de oportunidade de diagnóstico precoce, prevenção e/ou tratamento de condições genéticas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In other intervention implementation research in clinical genetics, acceptability has not been commonly examined or reported, with more studies focusing on patient centeredness or uptake (Roberts et al., 2017). In general, utilization of implementation theories and frameworks, including taxonomies of outcomes, is underutilized in the context of translational research in clinical genetics (Morrow et al., 2021; Paul et al., 2018; Roberts et al., 2017). This paucity of data makes it difficult to contextualize this subgroup finding and reinforces the need for more theory‐ or framework‐driven research to better understand how interventions impact different patients and what determinants influence patient, service, and implementation outcomes (Davidoff et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning barriers to genetic referral practices have examined both patient and practitioner factors. Now, a systematic review has examined approaches from the field of implementation science and how they have been applied to address suboptimal referral practices in the genetic setting (Morrow et al, 2021). The study results show that genetic referral interventions are rarely informed by implementation and/or behavior change theories and highlight the variable success of intervention efforts to improve genetic referral.…”
Section: Referencementioning
confidence: 99%